Research progress on using biological cathodes in microbial fuel cells for the treatment of wastewater containing heavy metals - Wang, Hui; Zhai, Pengxiang; Long, Xizi; Ma, Jianghang; Li, Yu; Liu, Bo; Xu, Zhiqiang (Frontiers in Microbiology, 2023)
Various types of electroactive microorganisms can be enriched to form biocathodes that reduce charge-transfer resistance, thereby accelerating electron transfer to heavy metal ions with high redox potentials in microbial fuel cells.Microorganisms acting as biocatalysts on a biocathode can reduce the energy required for heavy metal reduction, thereby enabling the biocathode to achieve a lower reduction onset potential. Thus, when such heavy metals replace oxygen as the electron acceptor, the valence state and morphology of the heavy metals change under the reduction effect of the biocathode, realizing the high-efficiency treatment of heavy metal wastewater.This study reviews the mechanisms, primary influencing factors (e.g., electrode material, initial concentration of heavy metals, pH, and electrode potential), and characteristics of the microbial community of biocathodes and discusses the electron distribution and competition between microbial electrodes and heavy metals (electron acceptors) in biocathodes. Biocathodes reduce the electrochemical overpotential in heavy metal reduction, permitting more electrons to be used. Our study will advance the scientific understanding of the electron transport mechanism of biocathodes and provide theoretical support for the use of biocathodes to purify heavy metal wastewater.